The Role of Media in Promoting Sustainable Tourism Practices - Mulyana, Hadi; Pradipta, Made Prasta Yostitia; Larisu, Zulfiah (PT. Anagata Sembagi Education, 2025)
This research is entitled The Role of Media in Promoting Sustainable Tourism Practices, which aims to understand the contribution of the media in increasing tourist awareness of the concept of sustainable tourism. The method used in this study is Systematic Literature Review (SLR), which allows the collection, analysis, and synthesis of various relevant research in a systematic manner. The SLR process involves identifying key research questions, literature search strategies from academic sources such as Google Scholar, Scopus, Web of Science, and ScienceDirect, as well as data analysis to identify trends, key findings, and research gaps in the field under review. The results of the study show that media, both traditional and digital, have a strategic role in the promotion of sustainable tourism. Digital media, such as social media, blogs, and vlogs, are effective tools in disseminating information and shaping tourists' perceptions of sustainable destinations. Meanwhile, traditional media remains relevant in reaching certain segments of tourists. However, there are several challenges in the implementation of media as a means of promoting sustainable tourism, including greenwashing practices that can mislead tourists and low awareness of sustainability among industry players. Therefore, collaboration between the government, industry players, and the public is needed in optimizing the role of the media to support socially responsible, economic, and environmentally responsible tourism practices. With the right strategy, the media can be an important instrument in ensuring the sustainability of the tourism sector and providing long-term benefits for all stakeholders